#TITLE_ALTERNATIVE# - Tri Panraya Purba (NIM : 15113002), Berlusconi
<palign="justify">NKRI waters have enormous potential to be developed and exploited with various activities, such as reclamation, navigation, infrastructure development, exploration, exploitation or energy industry, etc. The study area of this research is around Bangka Belitung waters as the operational area of tin exploration and exploitation.This final project is intended to learn and analyze the characteristics of ocean tide around Bangka Belitung waters by using the method of least square harmonic analysis of parameters. The tidal data used of this study are observed from two tidal stations with details of one on the Muntok Station (Bangka) and one on the Tanjungpandan Station (Belitung) where the length of its data for two years (2015−2016) with an interval of one-hour.The waters of Bangka Belitung are influenced by spatial variation with the fluctuation of the largest amplitude value of the main constituent K1 with the declination of the moon and solar system. The distance between the tidal stations is 286,916 km. The characteristics of tides between the stations are not homogeneous or the tide conditions are different. The temporal variation that occurs is a single pure diurnal/pure diary. The phase relationships of K1 and O1 are most dominant with periods of high and low respectively for 12 hours 25 minutes. Z0 value around the waters of Muntok station is 2,302 m and Tanjungpandan station is 1,480 m and this value is assumed to be constant. The impact of S0 value on tidal correction is highly significant due to its dynamic value and this is also influenced by sea water level which value varies depending on the time, the amount of data and source of errors affecting the accuracy of tidal data.<palign="justify">